Kuiluinī khetʻ ūʺ toʻ lhanʻ reʺ samuiṅʻʺ vaṅʻ ʼājānaññʻ myāʺ - ʼEʺ Sanʻʹ, Takkasuilʻ (ʼA vuiṅʻʺ Cā pe Tuikʻ, 1969)
Biographies of the Burmese revolutionaries of the early period of British occupation of Burma, 1824-1948.